A New Genus of Andean Katydid with Unusual Pronotal Structure for Enhancing Resonances - Fabio A. Sarria-Sarria; Glenn K. Morris; Fernando Montealegre-Z (Biology)
Katydids employ acoustic signals to communicate with others of their species and have evolved to generate sounds by coupling the anatomical structures of their forewings. However, some species have evolved to implement an additional resonance mechanism that enhances the transmission and sound pressure of the acoustic signals produced by the primary resonators. Secondary resonators, such as burrow cavities or horn-shaped structures, are found in the surrounding environment but could also occur as anatomical modifications of their bodies. Chamber-like structures have been described in species of katydids with modified pronota or wings. It has been shown that these modified structures directly affect the transmission and filtering of acoustic signals and can function as a Helmholtz resonator that encapsulates the primary sound source. By morphological and acoustic analysis, we describe a new genus of Conocephalinae and investigate the physical properties of their sound production structures for three new species from the Andes of Colombia and Ecuador. Males of the new genus, here described as Tectucantus n. gen., have a characteristic inflated pronotum enclosing the reduced first pair of wings and extending rearward over the first abdominal segments. We test the hypothesis that the pronotal cavity volume correlates with the carrier frequency of specific calls. The cavity of the pronotal chamber acts as a Helmholtz resonator in all three Tectucantus species and, potentially, in other distantly related species, which use similar secondary body resonators.